Autograft superior to both irradiated and non-irradiated allograft for primary ACL reconstruction: a systematic review. Issue 5 (18th August 2017) - Lording, Timothy; Steiner, Joel; Hewison, Christopher; Neyret, Philippe; Lustig, Sebastien
Abstract : Importance: Graft choice in anterior cruciate ligament (ACL) reconstruction is controversial. Recent evidence questions the equivalence of non-irradiated allografts to autografts in primary reconstruction. Aim: To compare the clinical outcomes of primary ACL reconstruction using autografts and allografts. Evidence review: A computerised search of the Pubmed/Medline, Cochrane Central Register of Controlled Trials, and SCOPUS databases was performed. We included comparative studies with level of evidence I to III, minimum 2 year follow-up, a minimum of 20 patients in each treatment arm, and selected outcome measures. Non-irradiated, non-chemically treated allografts and irradiated or chemically treated allografts were compared with autografts. The Cochrane Collaboration tool was used for quality appraisal. Findings: Twenty-two studies were included for the systematic review. These included 1148 autografts, 939 non-irradiated, non-chemically treated allografts, and 308 irradiated or chemically treated allografts. The failure rates for both allograft groups were inferior to that of autograft, with the OR for failure favouring autografts versus non-irradiated, non-chemically treated allografts (OR 0.51, 95% CI 0.30 to 0.88), and irradiated or chemically treated allografts (OR 0.12, 95% CI 0.06 to 0.21). Other outcome measures, including the Lachman test, pivot shift, instrumented laxity testing, and IKDC scores demonstrated no statistically significant differences for autograft and non-irradiated, non-chemically treated allograft reconstructions. Irradiated and chemically treated allograft reconstructions were inferior to autograft reconstructions in almost every examined outcome measure. Conclusions and relevance: In this level III systematic review, autograft reconstructions have a lower failure rate than both non-irradiated and irradiated allografts, particularly for younger patients. Other clinical outcome measures for autografts and non-irradiated allografts are not significantly different. Based on our results, it appears that irradiated and chemically-treated allografts have clearly inferior results, and surgeons should exercise caution when recommending ACL reconstruction with these allografts. Level of evidence: III.